2016
DOI: 10.2298/bah1601071k
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and mycotoxin contamination of maize hybrids in different maturity groups

Abstract: In the present study, the frequency of toxigenic fungi and occurrence of aflatoxin B1 (AFB1), deoxynivalenol (DON) and total fumonisins (FBs) in the kernels of six maize hybrids from different FAO maturity groups (ZP 341, ZP 427, ZP 434, ZP 560, ZP 606, ZP 666) in three localities (Belosavci, Ladjevci and Divci) in Serbia, during the harvest in 2013, was investigated. Using standard mycological tests of maize kernels, the presence of potentially toxigenic fungi species from the genera Aspergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The summary of analysis of annual and multi‐years results of occurrence, the presence and frequency of potentially toxigenic fungi and their mycotoxins in feeds is important primarily because of the implementation of preventive measures, as well as increasing the awareness of the consequences of the harmful effects of these contaminants in the food chain. To prevent the biosynthesis of mycotoxins, it is necessary to take measures that inhibit the development of fungi in the field (Krnjaja et al, ). The most important preventive measure is the cultivation of resistant cultivars and/or different forms of nitrogen fertilizers; therefore, continuous research of the sensitivity of domestic hybrids to toxigenic fungal species is required.…”
Section: Discussionmentioning
confidence: 99%
“…The summary of analysis of annual and multi‐years results of occurrence, the presence and frequency of potentially toxigenic fungi and their mycotoxins in feeds is important primarily because of the implementation of preventive measures, as well as increasing the awareness of the consequences of the harmful effects of these contaminants in the food chain. To prevent the biosynthesis of mycotoxins, it is necessary to take measures that inhibit the development of fungi in the field (Krnjaja et al, ). The most important preventive measure is the cultivation of resistant cultivars and/or different forms of nitrogen fertilizers; therefore, continuous research of the sensitivity of domestic hybrids to toxigenic fungal species is required.…”
Section: Discussionmentioning
confidence: 99%
“…Leggieri et al (2015) found that there were no significant differences in the aflatoxins level between maize hybrids from different FAO maturity groups in two-year trials (2009)(2010)(2011). Also, in Serbia, in 2013, Krnjaja et al (2016 have demonstrated that there were no significant effects of hybrids and the interaction effect of hybrids and location on the level of AFB 1 in the maize hybrids from FAO 300, 400, 500, and 600 maturity groups. Means followed by the same letter within a column are not significantly different according to Tukey's multiple comparison test (P ≤ 0.05); ** -significant at the 0.01 level of probability, *significant at the 0.05 level of probability, nsnot statistically significant…”
Section: Graphic 1 Mean Monthly Temperatures Total Monthly Rainfallmentioning
confidence: 98%